A hundred thousand welcomes - Donovan, Mary Lee; Cho, Lian (New York : Greenwillow Books, an imprint of HarperCollins Publishers, 2021)
Introduces scenes of hospitality and the word for "welcome" in more than twelve languages and cultures. Includes a pronunciation guide and information about the languages featured in the book.
Includes fold-out pages.
Includes bibliographical references.
K-3.
Keywords: Hospitality -- Juvenile fiction; Hospitality -- Fiction; Multiculturalism -- Fiction; Cultural pluralism -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Toleration -- Juvenile fiction